ANALISIS AKTIVA PAJAK TANGGUHAN DAN DISCRETIONARY ACCRUAL SEBAGAI PREDIKTOR MANAJEMEN LABA - Amik Murniyati, 10.05.52.0115; Nuswandari, Cahyani (Students Journal of Accounting and Banking, 2014)
The purpose of this study was to test the effect of deferred tax assets and discretionary accruals to the prediction of earnings manangement in perspective of agency theory and information asymmetry. The population in this study is manufacturing companies listed on the BEI (Bursa Efek Indonesia) with the observation period in 2010-2012. Sampling was purposive sampling method and the number of samples used as many as 52 observations. The analytical tool used is logistic regression. The result is the deferred tax assets have no significant effect, while discretionary accruals have a significant influence on the predictors of earnings management. This suggests that the use of discretionary accruals as earnings management prediction still valid.Keywords: Earnings management, deferred tax assets and discretionary accruals